The surface structure of TiO2(210) studied by atomically resolved STM and atomistic simulation - Howard, A; Mitchell, C; Morris, D; Egdell, R; Parker, S (2000)
The (210) surface of rutile (TiO2) has been studied by the experimental techniques of scanning tunnelling microscopy (STM), low energy electron diffraction (LEED) and X-ray photoelectron spectroscopy and by atomistic simulation. Atomic scale imaging in STM is most easily achieved at positive sample bias, thereby sampling empty electronic states. Images from surfaces prepared by ion bombardment and UHV annealing are dominated by terraces supporting bright rows with a ∼ 10 Å separation along the [120] direction as expected for a (1 × 1) reconstruction. The STM images are interpreted in terms of a structure with a lower energy than found in previous atomistic simulation studies. This is built up from {110} nanofacets of dimension a/√2 and 3a/√2, where a is the tetragonal lattice parameter. Several characteristic defect features on the TiO2(210) (1 × 1) surface are discussed in relation to this model. LEED indicates that superstructures involving periodicities of up to 50 Å along [120] co-exist with the (1 × 1) terraces, particularly after prolonged annealing in UHV. Some of these enlarged nanofacets have also been imaged by STM.